Abundance, population density and spatial ecology of mound-building termites in moist tropical deciduous forests of northern India. Issue 3 (2nd July 2020) - Singh Chakraborty, Joyeeta; Singh, Sudhir
ABSTRACT: Mound-building termites are ecosystem engineers whose abundance and spatial ecology are not adequately addressed in many forest ecosystems. We studied Odontotermes obesus mounds at two moist tropical deciduous forests (pure Sal and Sal-Teak mixed) in the Doon valley, northern India. Mound abundance, spatial pattern and termite population density were determined by direct count, nearest neighbour analyses and destructive sampling, respectively. Relations between mound attributes and stand characteristics such as woody vegetation diversity, density and tree stumps (representing food quality, quantity, open-space availability and disturbance) were tested at fine spatial scale using regression analyses. Active mounds were more abundant in the pure Sal stand ( 8.0 mounds/ha) than in the mixed stand ( 5.0 mounds/ha). Mean population density (both sites combined) was 2.01 × 10 5 individuals per mound. Population density was strongly correlated with mound volume. Predominance of young colonies was indicated by high occurrence (≥ = 65%) of small mounds (< 1.25 m 3 ). Mounds were predominantly randomly distributed. However, the pure Sal stand showed a partial tendency towards aggregation. Our results revealed that woody species richness is an important, site-specific regulatory factor. Local-scale variations should be cautiously considered while up-scaling the contribution of O. obesus mounds to various ecosystem processes.